Tocotrienol in the Treatment of Topical Wounds: Recent Updates - Anroop B. Nair; Bapi Gorain; Manisha Pandey; Shery Jacob; Pottathil Shinu; Bandar Aldhubiab; Rashed M. Almuqbil; Heba S. Elsewedy; Mohamed A. Morsy (MDPI AG, 2022)
Healing wounds is an important attempt to keep the internal higher organs safe. Complications in topical wound healing may lead to the formation of scars, which can affect the patient's quality of life. Although several approaches are ongoing in parallel in the exploration of natural compounds via advanced delivery, in this article, an attempt has been made to highlight tocotrienol. Tocotrienol is a natural form of vitamin E and has shown its potential in certain pharmacological activities better than tocopherol. Its antioxidant, anti-inflammatory, cell signal-mediating effects, angiogenic properties, management of scar, and promotion of wound environment with essential factors have shown potential in the management of topical wound healing. Therefore, this review has aimed to focus on recent advances in topical wound healing through the application of tocotrienols. Challenges in delivering tocotrienols to the topical wound due to its large molecular weight and higher logP have also been explored using nanotechnological-based carriers, which has made tocotrienol a potential tool to facilitate the closure of wounds. Exploration of tocotrienol has also been made in human volunteers for biopsy wounds; however, the results are yet to be reported. Overall, based on the current findings in the literature, it could be inferred that tocotrienol would be a viable alternative to the existing wound dressing components for the management of topical wounds.